2019
DOI: 10.1111/sode.12368
|View full text |Cite
|
Sign up to set email alerts
|

Within‐ and between‐individual variation in fathers’ emotional expressivity in Chinese families: Contributions of children’s emotional expressivity and fathers’ emotion‐related beliefs and perceptions

Abstract: Parental emotion socialization is a dynamic process encompassing moment-to-moment fluctuations in parents' emotional displays and responsiveness. This study attempted to examine the within-and between-individual variation in fathers' emotional expressivity during a real-time father-child interaction in Chinese families. Eighty-five children (M age = 7.58 years, SD = 0.50 years, 47.1% boys) from east China and their biological fathers participated in the study.Fathers' and children's emotional expressivity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Parents and children react to each other's behavior and emotions, and the gradual effect of these interactions triggers specific dynamics between parent and child (Chow et al, 2010). Research has found that the emotional responses of parents and the emotional regulation of children are mutually influential during emotional discussions (Li & Li, 2019; Morelen & Suveg, 2012), and that the physiological responses of parents and children are mutually strengthened over time (Lunkenheimer et al, 2018). During these interactions, the tendency of the child to resist the parent's wishes activates negative parental emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Parents and children react to each other's behavior and emotions, and the gradual effect of these interactions triggers specific dynamics between parent and child (Chow et al, 2010). Research has found that the emotional responses of parents and the emotional regulation of children are mutually influential during emotional discussions (Li & Li, 2019; Morelen & Suveg, 2012), and that the physiological responses of parents and children are mutually strengthened over time (Lunkenheimer et al, 2018). During these interactions, the tendency of the child to resist the parent's wishes activates negative parental emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Although Chinese mothers are still perceived to be warmer and less harsh than Chinese fathers (Chen, Liu, & Li, 2000; Lau, Lew, Hau, Cheung, & Berndt, 1990; Shek, 1998; Strom, Strom, & Xie, 1996), numerous studies documented the gradual erosion of the stern, aloof image of the traditional Chinese father. D. Li and Li’s (2018) recent observational study of the father–child play captured fathers’ exhibition of positive affect as they played with their children.…”
Section: Chinese Fathers’ Expression Of Warmth: Contemporary Contextsmentioning
confidence: 99%